2016
DOI: 10.5194/bg-13-5917-2016
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of coccolithophore abundance and calcification across Drake Passage (Southern Ocean)

Abstract: Abstract. Although coccolithophores are not as numerically common or as diverse in the Southern Ocean as they are in subpolar waters of the North Atlantic, a few species, such as Emiliania huxleyi, are found during the summer months. Little is actually known about the calcite production (CP) of these communities or how their distribution and physiology relate to environmental variables in this region. In February 2009, we made observations across Drake Passage (between South America and the Antarctic Peninsula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 82 publications
(182 reference statements)
7
57
0
4
Order By: Relevance
“…This problem of correlations among drivers has been noted before in examining transect data across the Drake Passage, where more detailed measurements of coccolithophore properties augmented with incubation studies found that temperature and light were the most probable drivers of coccolithophore abundance and calcification rates (Charalampopoulou et al, 2016). Our lack of information on the availability of light (mixed layer depth was determined only on the two hydrographic sections), iron, or individual species and strains makes deducing a possible influence of ocean acidification on coccolithophore distributions from our spatial distribution data even more difficult.…”
Section: Comparison To Possible Environmental Controls On Coccolithopmentioning
confidence: 89%
See 2 more Smart Citations
“…This problem of correlations among drivers has been noted before in examining transect data across the Drake Passage, where more detailed measurements of coccolithophore properties augmented with incubation studies found that temperature and light were the most probable drivers of coccolithophore abundance and calcification rates (Charalampopoulou et al, 2016). Our lack of information on the availability of light (mixed layer depth was determined only on the two hydrographic sections), iron, or individual species and strains makes deducing a possible influence of ocean acidification on coccolithophore distributions from our spatial distribution data even more difficult.…”
Section: Comparison To Possible Environmental Controls On Coccolithopmentioning
confidence: 89%
“…Further progress in understanding the controls on coccolithophore abundances in the Southern Ocean is clearly needed. At present, temperature, light and competition with diatoms for iron appear to be the strongest candidates (at least for southward expansion (Charalampopoulou et al, 2016;Gafar et al, 2017; with nitrate a strong influence on the location of the northern oligotrophic boundary : Feng et al, 2016).…”
Section: Comparison To Possible Environmental Controls On Coccolithopmentioning
confidence: 94%
See 1 more Smart Citation
“…Evidence from in situ and satellite observations indicates that E. huxleyi has been increasingly expanding its range poleward in both hemispheres over the last two decades, and contributing factors to this poleward expansion may differ between regions and hemispheres (Winter et al, 2014). For example, warming and freshening have promoted E. huxleyi blooms in the Bering Sea since the late 1970s (Harada et al, 2012), while temperature and irradiance were best able to explain variability in E. huxleyi-dominated coccolithophore community composition and abundance across the Drake Passage (Southern Ocean) (Charalampopoulou et al, 2016). Hence, empirical data on the responses of E. huxleyi to different environmental drivers would be critical for fully understanding the roles of this prominent coccolithophore species in marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier field studies have also analyzed linkages between carbonate chemistry and species composition in an OA context using multivariate statistics (e.g. Charalampopoulou et al (2011);Charalampopoulou et al (2016)). Frigstad et al (2013) reported the need for comprehensive studies on all available environmental data (with lots of variables) to determine causal relationships.…”
Section: Introductionmentioning
confidence: 99%